Insurgent bodies: Andrea Giunta launches book in which she shows na expressive panorama of feminist art in Latin America (Palíndromo, 2022)
Understanding the complex problems surrounding the representation of women in the world of art, especially in Latin America, is the main contribution of the book “Feminism and Latin American Art - stories of artists who emancipated the body”, of the researcher and curator Andrea Giunta. launched in 2018 in Argentina. With extensive quantitative data and a rigorous theoretical analysis, Giunta gives an incisive panel on the role of many artists in the region and their legacy for the deconstruction of the patriarchal canon. Avoiding fragile generalizations, simplifying essentialisms and common places about feminist art, the researcher uses different perspectives, such as the relationship between political activism and feminist activism, the differentiation between feminist art and feminine art, the new agenda for self-portrait in the egocentric, social stereotypes of the female and prostitute. In this way, the work highlights by its pioneer spirit in condensing - from a comparative study with precedents among artists from different countries - a posible history of Latin American feminist art.
Keywords: Feminist art; Latin American art; Women artists; Art history; Decolonialist art